Genetic Deletion of IL-19 (Interleukin-19) Exacerbates Atherogenesis in Il19 -/- × Ldlr -/- Double Knockout Mice by Dysregulation of mRNA Stability Protein HuR (Human Antigen R) - Ray, Mitali; Gabunia, Khatuna; Vrakas, Christine N; Herman, Allison B; Kako, Farah; Kelemen, Sheri E; Grisanti, Laurel A; Autieri, Michael V (Arteriosclerosis, thrombosis, and vascular biology, 2018)
To test the hypothesis that loss of IL-19 (interleukin-19) exacerbates atherosclerosis. APPROACH AND RESULTS: mice were crossed into (low-density lipoprotein receptor knock out) mice. Double knockout (dKO) mice had increased plaque burden in aortic arch and root compared with controls after 14 weeks of high-fat diet (HFD). dKO mice injected with 10 ng/g per day rmIL-19 had significantly less plaque compared with controls. qRT-PCR and Western blot analysis revealed dKO mice had increased systemic and intraplaque polarization of T cells and macrophages to proinflammatory T 1 and M1 phenotypes, and also significantly increased TNF (tumor necrosis factor)-α expression in spleen and aortic arch compared with controls. Bone marrow transplantation suggests that immune cells participate in IL-19 protection. Bone marrow-derived macrophages and vascular smooth muscle cells isolated from dKO mice had a significantly greater expression of inflammatory cytokine mRNA and protein compared with controls. Spleen and aortic arch from dKO mice had significantly increased expression of the mRNA stability protein HuR (human antigen R). Bone marrow-derived macrophage and vascular smooth muscle cell isolated from dKO mice also had greater HuR abundance. HuR stabilizes proinflammatory transcripts by binding AU-rich elements in the 3' untranslated region. Cytokine and HuR mRNA stability were increased in dKO bone marrow-derived macrophage and vascular smooth muscle cell, which was rescued by addition of IL-19 to these cells. IL-19-induced expression of miR133a, which targets and reduced HuR abundance; miR133a levels were lower in dKO mice compared with controls. These data indicate that IL-19 is an atheroprotective cytokine which decreases the abundance of HuR, leading to reduced inflammatory mRNA stability.